Preparation method of modified silica sol and inorganic porcelainized coating adopting modified silica sol

By modifying silicone sols with silicone and nano-alumina and combining acrylic emulsions and other materials, the problems of porous surfaces and poor stain resistance on conventional inorganic coatings are solved, and inorganic coatings with high stain resistance, high hardness and high bonding strength are prepared, which is suitable for public areas.

CN119613987APending Publication Date: 2025-03-14JIANGSU SOBUTE NEW MATERIALS CO LTD +1

Patent Information

Application Number
CN202311183944.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Conventional inorganic coatings have porous surfaces, are prone to accumulation of dirt, and have poor stain resistance. It is difficult to meet the requirements of high stain resistance in public areas.

Method used

Silicone modified silicon sol and nano alumina is added on the basis to improve the film forming performance and hardness of the silicon sol, and acrylic emulsion and various fillers and additives are combined to prepare inorganic coatings with high stain resistance.

Benefits of technology

It achieves high stain resistance of the paint, with adhesive strength greater than 1.5 MPa, hardness greater than 6H, and wash resistance greater than 20,000 times. It is easy to wipe common stains and has excellent overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613987A_ABST
    Figure CN119613987A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of modified silica sol and an inorganic porcelainized coating adopting the modified silica sol. The inorganic porcelainized coating is prepared from modified silica sol, acrylic emulsion, cellulose, solid filler, bentonite, auxiliaries, AMP-95, an organic silicon water repellent agent and ionized water, a preparation method of the modified silica sol comprises the steps that siloxane is grafted to the silica sol through a sol-gel method, then a nanometer aluminum oxide aqueous solution is added, and the modified silica sol is prepared through a sol-gel method. Performing ultrasonic treatment after stirring to obtain the modified silica sol. Silica sol is modified through siloxane and nanometer aluminum oxide, the film forming performance of the silica sol is effectively improved, the silica sol has the extremely high hardness and hydrophobic effect, and then the inorganic coating prepared by compounding the acrylic emulsion and various filler and auxiliaries is large in strength, high in hardness, excellent in scrubbing resistance and good in stain resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of inorganic building coatings, in particular to a stain-resistant, high-hardness inorganic building coating, and specifically to a preparation method of a modified silica sol and a high-hardness, stain-resistant inorganic porcelain coating using the modified silica sol. Background Art

[0002] With the release and implementation of GB 50222-2017 "Code for Fire Protection of Interior Design of Building Decoration", the standard has clear requirements for the combustion performance level of decorative materials for ceilings and walls of special buildings, civil buildings, and factory warehouses. Most of them are required to reach Class A (non-flammable). Among the many architectural coatings, inorganic coatings have attracted much attention due to their excellent natural fire resistance. Inorganic coatings usually refer to a type of coating with inorganic materials as the main film-forming substance or binder, and the commonly used inorganic film-forming substances in architectural coatings are mainly silicates. Inorganic silicate coatings have excellent fire resistance because they contain little or no organic matter. At the same time, they have excellent weather resistance, antibacterial and mildew-proof, and are breathable and waterproof.

[0003] Patent CN115948063A discloses a silicate-modified silica sol-based water-based inorganic coating. The present invention chemically compounds a silicate film-forming material with silica sol by an emulsion blending method to construct a fibrous structural network with a high degree of condensation, high tensile strength and good water resistance. The fibrous structural network has enhanced bonding ability with the wall substrate, cures at room temperature, is not prone to cracks, and has enhanced water resistance of the coating.

[0004] Patent CN110204932B discloses a water-based silicate composite thermal insulation flame retardant coating and a preparation method thereof. The water-based silicate composite thermal insulation flame retardant coating is based on an inorganic nano-silicate resin, and is formulated with a silicate water-based thixotropic agent, a polycarbodiimide cross-linking agent, nano-aerogel powder and other components to provide the coating with excellent adhesion, good alkali resistance, good weather resistance, thermal insulation flame retardant properties, antibacterial function and super hardness, and is multifunctional, easy to construct and low in cost.

[0005] However, conventional inorganic coatings have porous surfaces, are prone to dirt accumulation, and have poor stain resistance. At the same time, inorganic coatings are widely used in public areas such as shopping malls, schools, and hospitals, which put forward higher requirements for stain resistance. Therefore, it is urgent to design an inorganic coating with high stain resistance. Summary of the invention

[0006] Aiming at the problems that conventional silica sol has poor film-forming property and is easy to crack, and that traditional inorganic coating has porous surface and poor stain resistance, the present invention adopts siloxane-modified silica sol to solve the problem of poor film-forming property of silica sol, and further uses nano-alumina to modify the silica sol, thereby further improving the hardness and hydrophobic effect of the silica sol. Acrylic emulsion is compounded, and various fillers, pigments and additives are added to design and prepare an inorganic coating with high stain resistance. The inorganic coating has a bonding strength of more than 1.5 MPa, a hardness of more than 6H, and a washing resistance of more than 20,000 times. It is easy to wipe off common stains such as water-based pens, soy sauce, beverages, iodine tincture, etc., and has excellent comprehensive stain resistance.

[0007] The present invention provides a method for preparing a modified silica sol, comprising the following steps:

[0008] (1) Grafting siloxane onto silica sol by sol-gel method: first, adding a pH adjuster to the silica sol to adjust the pH value of the silica sol to 3-4, then adding an alcohol solvent to obtain a silica sol solution; adding siloxane dropwise to the silica sol solution, heating it to a certain temperature in a water bath and stirring it to obtain siloxane-modified silica sol. After the siloxane is hydrolyzed in the solution, it reacts with the silanol group in the silica sol, which can effectively improve the film-forming performance of the silica sol;

[0009] The mass ratio of siloxane to silica sol in step (1) is 0.1-0.5:1, and the solid content of the silica sol is 32±2%;

[0010] The alcohol solvent is used in an amount of 10% of the mass of the silica sol, preferably n-butanol or isopropanol;

[0011] The water bath heating temperature is 60-80°C, the stirring speed is 300r / min, and the stirring time is 3-4h;

[0012] (2) adding a nano-alumina aqueous solution to the siloxane-modified silica sol obtained in step (1), stirring and then ultrasonicating to obtain a modified silica sol;

[0013] The mass ratio of the nano-alumina aqueous solution to the siloxane-modified silica sol in step (2) is 0.1-0.6:1; the solid content of the nano-alumina aqueous solution is 10wt%-40wt%;

[0014] In step (2), the stirring speed is 300-400 r / min, the stirring time is 1-2 h, and the ultrasonic time is 30 min.

[0015] The siloxane in step (1) is selected from any one or more of methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane.

[0016] The pH adjusting agent in step (1) is selected from any one or more of nitric acid, hydrochloric acid, sulfuric acid, acetic acid, oxalic acid and citric acid aqueous solutions.

[0017] The present invention also provides an inorganic porcelain coating of modified silica sol prepared by the above method, comprising the following components, and the mass fractions of each component are as follows:

[0018]

[0019] The balance is deionized water.

[0020] The total weight of the above components is 1000 parts.

[0021] The AMP-95 is a multifunctional amine auxiliary agent.

[0022] Furthermore, the acrylic emulsion of the present invention is selected from any one or more of styrene acrylic emulsion, pure acrylic emulsion, and silicone acrylic emulsion, and the MFFT is less than 25°C;

[0023] Furthermore, the cellulose described in the present invention is nonionic cellulose or anionic cellulose, wherein the nonionic cellulose is selected from a mixture of any one or more of nonionic hydroxyethyl cellulose, nonionic hydroxypropyl cellulose, nonionic hydroxymethyl cellulose, nonionic methyl cellulose, and nonionic ethyl cellulose, and the anionic cellulose is selected from a mixture of any one or more of anionic hydroxyethyl cellulose, anionic hydroxypropyl cellulose, anionic hydroxymethyl cellulose, anionic methyl cellulose, and anionic ethyl cellulose.

[0024] Furthermore, the solid filler of the present invention is selected from any one or more of titanium dioxide, talc, kaolin, heavy calcium and mica powder.

[0025] Furthermore, the auxiliary agent of the present invention includes a wetting and dispersing agent and a defoaming agent, wherein the wetting and dispersing agent is a high molecular weight block copolymer containing pigment affinity groups, and the defoaming agent is selected from a mixture of any one or more of mineral oils, silicones, silicone polyethers, and non-silicone defoaming agents.

[0026] The present invention also provides a method for preparing the above-mentioned inorganic porcelain coating, comprising:

[0027] Add cellulose and AMP-95 to deionized water, stir for 5-10 minutes at a speed of 300-700 r / min, add the first batch of defoamer and wetting dispersant after the cellulose is swollen, and disperse for 5-10 minutes at a speed of 300-700 r / min; then add solid filler and bentonite, adjust the speed to 1000-200 r / min, stir and disperse for 30-60 minutes to reduce the fineness to less than 60 μm; adjust the speed to 300-700 r / min, add the second batch of defoamer and acrylic emulsion in turn, stir and disperse for 5-10 minutes; then add modified silica sol, stir for 5-10 minutes, and then gradually add organosilicon hydrophobic agent and the third batch of defoamer, stir evenly and control the viscosity at 80-95 KU to obtain an inorganic coating.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention utilizes siloxane and nano-alumina to modify the silica sol, effectively improving the film-forming performance of the silica sol, and having extremely high hardness and hydrophobic effect, and then compounding acrylic emulsion and various fillers and additives to prepare the inorganic coating, which has high strength, high hardness, excellent washability and good stain resistance.

[0030] Silica sol has silicon-oxygen bonds as the main chain segments, with high bond energy, and its three-dimensional crystal structure has high hardness, but it is easy to crack into powder during the curing process and cannot form a film effectively. Conventional inorganic coatings usually need to be compounded with a certain amount of potassium silicate to improve the adhesion of the coating, but potassium silicate has high alkalinity and poor compatibility with emulsions and various additives, and the coating is easy to salt out, affecting the appearance. Therefore, we modify the silica sol with siloxanes such as methyltriethoxysilane and methyltrimethoxysilane. Siloxanes are hydrolyzed in the aqueous silica sol and react with the hydroxyl groups in the silica sol. The modified silica sol has high stability and excellent film-forming properties. Adding nano-alumina aqueous solution for the next step of modification can improve the hardness and hydrophobicity of the silica sol. The inorganic coating prepared by compounding acrylic emulsion has high overall hardness, good water resistance, and washability of more than 20,000 times. It is easy to wipe off common stains such as water-based pens, soy sauce, beverages, and iodine tincture. At the same time, compounding emulsion in inorganic ceramic coatings will improve the overall flexibility and crack resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The figures are before, during and after the stain-resistant coating is prepared on cement board using the coating described in Example 1 of the present invention.

[0032] Figure 2 These are the before, during and after effects of using the coating described in Example 2 of the present invention to prepare a stain-resistant coating on a cement board.

[0033] Figure 3These are the before, during and after effects of using the coating described in Example 3 of the present invention to prepare a stain-resistant coating on a cement board.

[0034] Figure 4 The figures are before, during and after the stain resistance of a coating prepared on a cement board using the coating described in the comparative example of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The amounts of the components in the following examples are in parts by mass.

[0037] Example 1

[0038] A method for preparing an inorganic ceramic coating using modified silica sol comprises:

[0039] (1) Preparation of modified silica sol: Weigh 100 parts of silica sol, add 2% oxalic acid aqueous solution to adjust the pH to 3, add 10 parts of isopropanol as a solvent at room temperature to obtain a silica sol aqueous solution; then add 10 parts of methyltriethoxysilane at 80°C, stir at 300 r / min for 3 hours to obtain siloxane-modified silica sol; add 10 parts of nano-alumina aqueous solution with a solid content of 25% to the above siloxane-modified silica sol, stir at 300 r / min for 1 hour, and then ultrasonically disperse for 30 minutes to obtain the final modified silica sol product;

[0040] (2) Preparation of inorganic porcelain coating: Then, 6 g of nonionic hydroxyethyl cellulose and 1 g of AMP-95 were added to 466 g of deionized water, and stirred at a speed of 500 r / min for 5 min. After the cellulose was swollen, 2 g of mineral oil defoamer and 4 g of wetting dispersant were added, and dispersed at a speed of 500 r / min for 10 min; then 100 g of titanium dioxide, 85 g of kaolin, 150 g of heavy calcium and 4 g of bentonite were added, and the speed was adjusted to 1500 r / min, and the mixture was stirred and dispersed for 30 min to reduce the fineness to less than 60 μm; the speed was adjusted to 600 r / min, and 2 g of mineral oil defoamer and 20 g of styrene-acrylic emulsion were added in sequence, and stirred and dispersed for 10 min; then 150 g of the above-mentioned modified silica sol was added, and stirred for 10 min, and then 10 g of organosilicon hydrophobic agent and 2 g of mineral oil defoamer were gradually added, and the mixture was stirred evenly and the viscosity was controlled at 87 KU to obtain an inorganic coating.

[0041] The coating was scraped onto the non-asbestos fiber cement board using a 120μm and 80μm wire rod. It was completely dry in 30 minutes and the performance test was performed after curing for 7 days. The stain resistance test is shown in the attached Figure 1 .

[0042] Example 2

[0043] A method for preparing an inorganic ceramic coating using modified silica sol comprises:

[0044] (1) Preparation of modified silica sol: Weigh 100 parts of silica sol, add 2% citric acid aqueous solution to adjust the pH to 3, add 10 parts of n-butanol as a solvent at room temperature to obtain a silica sol aqueous solution; then add 50 parts of methyltrimethoxysilane at 80°C, stir at 300 r / min for 4 hours to obtain siloxane-modified silica sol; add 60 parts of nano-alumina aqueous solution with a solid content of 25% to the above siloxane-modified silica sol, stir at 300 r / min for 2 hours, and then ultrasonically disperse for 30 minutes to obtain the final modified silica sol product;

[0045] (2) Preparation of inorganic coating: 6 g of anionic hydroxyethyl cellulose and 0.5 g of AMP-95 were added to 240 g of deionized water, and stirred at a speed of 500 r / min for 5 min. After the cellulose was swollen, 2 g of silicone defoamer and 4 g of wetting dispersant were added, and dispersed at a speed of 500 r / min for 10 min. Then, 100 g of titanium dioxide, 85 g of kaolin, 150 g of heavy calcium and 6 g of bentonite were added, and the speed was adjusted to 1500 r / min. The mixture was stirred and dispersed for 30 min to reduce the fineness to less than 50 μm. The speed was adjusted to 600 r / min, and 2 g of silicone defoamer and 100 g of pure acrylic emulsion were added in sequence, and stirred and dispersed for 10 min. Then, 300 g of modified silica sol was added, and stirred for 10 min. Then, 10 g of silicone hydrophobic agent and 2 g of silicone defoamer were gradually added, and the mixture was stirred evenly and the viscosity was controlled at 85 KU to obtain an inorganic coating.

[0046] The coating was scraped onto the non-asbestos fiber cement board using a 120μm and 80μm wire rod. It was completely dry in 30 minutes and the performance test was performed after curing for 7 days. The stain resistance test is shown in the attached Figure 2 .

[0047] Example 3

[0048] A method for preparing an inorganic ceramic coating using modified silica sol comprises:

[0049] (1) Preparation of modified silica sol: Weigh 100 parts of silica sol, add 2% hydrochloric acid aqueous solution to adjust the pH to 3, add 10 parts of isopropanol as a solvent at room temperature to obtain a silica sol aqueous solution; then add 20 parts of dimethyldimethoxysilane at 60°C, stir at 300 r / min for 3 hours to obtain siloxane-modified silica sol; add 20 parts of nano-alumina aqueous solution with a solid content of 25% to the above siloxane-modified silica sol, stir at 300 r / min for 1 hour, and then ultrasonically disperse for 30 minutes to obtain the final modified silica sol product;

[0050] (2) Preparation of inorganic coating: 10 g of nonionic methyl cellulose and 2 g of AMP-95 were added to 234 g of deionized water, and stirred at a speed of 500 r / min for 5 min. After the cellulose was swollen, 4 g of silicone polyether defoamer and 8 g of wetting dispersant were added, and dispersed at a speed of 500 r / min for 10 min; then 50 g of titanium dioxide, 85 g of kaolin, 150 g of heavy calcium, 100 g of talcum powder, and 5 g of bentonite were added, and the speed was adjusted to 1500 r / min, and stirred and dispersed for 30 min to reduce the fineness to less than 50 μm; the speed was adjusted to 600 r / min, and 4 g of silicone polyether defoamer and 80 g of silicone acrylic emulsion were added in sequence, and stirred and dispersed for 10 min; then 250 g of modified silica sol was added, and stirred for 10 min, and then 20 g of silicone hydrophobic agent and 4 g of silicone polyether were gradually added, and stirred evenly and the viscosity was controlled at 85 KU to obtain an inorganic coating.

[0051] The coating was scraped onto the non-asbestos fiber cement board using a 120μm and 80μm wire rod. It was completely dry in 30 minutes and the performance test was performed after curing for 7 days. The stain resistance test is shown in the attached Figure 3 .

[0052] Comparative Example (Comparison with ordinary silica sol)

[0053] An inorganic coating is prepared as follows:

[0054] Add 6g of hydroxyethyl cellulose and 1g of AMP-95 to 380g of deionized water, stir for 5min at a speed of 500r / min, and after the cellulose is swollen, add 2g of defoamer and 4g of wetting dispersant, and disperse for 10min at a speed of 500r / min; then add 100g of rutile titanium dioxide, 85g of 1200 mesh kaolin, 150g of 800 mesh heavy calcium, and 4g of bentonite, adjust the speed to 1500r / min, and stir and disperse for 30min until the fineness is reduced to less than 50μm; adjust the speed to 600r / min, add 2g of defoamer and 80g of odorless styrene-acrylic emulsion in turn, stir and disperse for 10min; then add 200g of ordinary silica sol, stir for 10min, and then gradually add 10g of silicone hydrophobic agent and 2g of defoamer, stir evenly and control the viscosity at 87KU to obtain an inorganic coating.

[0055] The coating was scraped onto the non-asbestos fiber cement board using a 120μm and 80μm wire rod. It was completely dry in 30 minutes and the performance test was performed after curing for 7 days. The stain resistance test is shown in the attached Figure 4 .

[0056] By the attached Figure 1-4 It can be found that when the coating described in the embodiment of the present invention is used, the asbestos-free fiber cement board can be easily wiped clean of vinegar, soy sauce, cola, orange juice, iodine, ink, etc., while when the conventional inorganic coating of the comparative example is used, the cement board surface is porous and various water-based stains are easy to penetrate, and it cannot be wiped clean.

[0057] The performance of the asbestos-free fiber cement board coated with the coatings of each embodiment and comparative example was tested, and the results are shown in Table 1. From the data results in Table 1, it can be found that compared with the comparative example, the paint film hardness, flexibility, scrub resistance, bonding strength and stain resistance of the cement board using the coating of the embodiment are greatly improved.

[0058] Table 1 Performance test results of asbestos-free fiber cement boards coated with paints of various embodiments and comparative examples

[0059]

Claims

1. A method for preparing a modified silica sol, characterized in that: The steps include: (1) Grafting siloxane onto silica sol by a sol-gel method: first, adding a pH adjuster to the silica sol to adjust the pH value of the silica sol to 3-4, then adding an alcohol solvent to obtain a silica sol solution; adding siloxane dropwise to the silica sol solution, heating it in a water bath to a certain temperature and stirring it to obtain a siloxane-modified silica sol; The mass ratio of the siloxane to the silica sol is 0.1-0.5:1, and the solid content of the silica sol is 32±2%; (2) adding a nano-alumina aqueous solution to the siloxane-modified silica sol obtained in step (1), stirring and then ultrasonicating to obtain a modified silica sol; The mass ratio of the nano-alumina aqueous solution to the siloxane-modified silica sol is 0.1-0.6:1; and the solid content of the nano-alumina aqueous solution is 10wt%-40wt%.

2. The method for preparing a modified silica sol according to claim 1, characterized in that: The alcohol solvent used in step (1) is 10% of the mass of the silica sol, and the alcohol solvent is n-butanol or isopropanol; The water bath heating temperature is 60-80°C, the stirring speed is 300r / min, and the stirring time is 3-4h; In step (2), the stirring speed is 300-400 r / min, the stirring time is 1-2 h, and the ultrasonic time is 30 min.

3. The method for preparing a modified silica sol according to claim 2, characterized in that: The siloxane in step (1) is selected from any one or more of methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane.

4. The method for preparing a modified silica sol according to claim 3, characterized in that: The pH adjusting agent in step (1) is selected from any one or more of nitric acid, hydrochloric acid, sulfuric acid, acetic acid, oxalic acid and citric acid aqueous solutions.

5. An inorganic ceramic coating comprising the modified silica sol obtained by the method according to any one of claims 1 to 4, characterized in that: It includes the following components, and the mass fractions of each component are as follows: The total weight of the above components is 1000 parts.

6. An inorganic porcelain coating according to claim 5, characterized in that: The acrylic emulsion is selected from any one of styrene acrylic emulsion, pure acrylic emulsion, silicone acrylic emulsion and the like, and the MFFT is less than 25°C.

7. An inorganic porcelain coating according to claim 5, characterized in that: The cellulose is nonionic cellulose or anionic cellulose, wherein the nonionic cellulose is selected from a mixture of any one or more of nonionic hydroxyethyl cellulose, nonionic hydroxypropyl cellulose, nonionic hydroxymethyl cellulose, nonionic methyl cellulose, and nonionic ethyl cellulose, and the anionic cellulose is selected from a mixture of any one or more of anionic hydroxyethyl cellulose, anionic hydroxypropyl cellulose, anionic hydroxymethyl cellulose, anionic methyl cellulose, and anionic ethyl cellulose.

8. An inorganic ceramic coating according to claim 5, characterized in that: The solid filler is selected from any one or more of titanium dioxide, talc, kaolin, heavy calcium and mica powder.

9. An inorganic porcelain coating according to claim 5, characterized in that: The auxiliary agent includes a wetting and dispersing agent and a defoaming agent, wherein the wetting and dispersing agent is a high molecular weight block copolymer containing pigment affinity groups, and the defoaming agent is selected from any one or more of mineral oil, silicone, silicone polyether, and non-silicone defoaming agents.

10. A method for preparing the inorganic ceramic coating according to any one of claims 5 to 9, characterized in that: include: Add cellulose and AMP-95 to deionized water, stir for 5-10 minutes at a speed of 300-700 r / min, add the first batch of defoamer and wetting dispersant after the cellulose is swollen, and disperse for 5-10 minutes at a speed of 300-700 r / min; then add solid filler and bentonite, adjust the speed to 1000-200 r / min, stir and disperse for 30-60 minutes to reduce the fineness to less than 60 μm; adjust the speed to 300-700 r / min, add the second batch of defoamer and acrylic emulsion in sequence, stir and disperse for 5-10 minutes; then add modified silica sol, stir for 5-10 minutes, and then gradually add organosilicon hydrophobic agent and the third batch of defoamer, stir evenly and control the viscosity at 80-95 KU to obtain the inorganic porcelain coating.

Citation Information

Patent Citations

  • A water-based silicate composite heat-insulating and flame-retardant coating and its preparation method

    CN110204932B

  • Nanometer composite hydrophobic hard transparent film and preparation method thereof

    CN101629066A

  • Environmentally-friendly flame-retardant water-based inorganic coating for interior walls and preparation method of coating

    CN109722070A

  • Energy-saving environment-friendly inorganic building coating and preparation method thereof

    CN111961357A

  • High-water-resistance wear-resistant ceramic texture coating, preparation method and electronic appearance structural member

    CN113698806A

Cited By

  • Wear-resistant coating for machine tool cutter and preparation method of wear-resistant coating

    CN121160184A

  • Fluorine-containing polyether modified nano silica sol and composite silicate inorganic coating for hydraulic lime-based wall surface and preparation method of fluorine-containing polyether modified nano silica sol and composite silicate inorganic coating

    CN122356870A